Adopsi Teknologi Sambung Pucuk Pada Kopi Rakyat Berdasarkan Faktor Internal dan Ekternal Petani Lokal di Provinsi Bengkulu - Eddy Silamat; Hermanto Siregar; Rachmat Pambudy; Harianto Harianto (Postgraduate, University of Mataram, 2023)
The application of the practice of grafting technology to people's coffee plants is very encouraged by the people of Bengkulu Province. This of course cannot be separated from the factors that influence people in practicing grafting. Based on this phenomenon, this research was conducted to find out the internal and external factors that influence people to practice grafting in Bengkulu Province. This research is quantitative, primary data was obtained through a questionnaire by distributing a list of questions that had been prepared. The sample was selected using the multi-stage sampling method. The total number of frame samples was 326, consisting of 120 grafted frame samples and 206 coffee frame samples that had not been grafted. Coffee plants can be propagated vegetatively, that is, using parts of the plant itself, and generatively, that is, using seeds or grains. Grafting in coffee plants is vegetative propagation. The research results show that internal factors inherent in coffee farmers in Bengkulu are the dominant drivers in adopting grafting technology, that is the farmer's age, knowledge, experience in the field of grafting, convenience, and results obtained